REGRESI LOGISTIK ORDINAL (STUDI KASUS FAKTOR YANG MEMPENGARUHI TINGKAT STRES MAHASISWA DALAM MENYELESAIKAN SKRIPSI) - Fatonah, Laily; Sanapiah, Sanapiah; Febrilia, Baiq Rika Ayu (Media Pendidikan Matematika, 2017)
Stress is a condition that is susceptible to experienced by students who are completing a thesis. The results of preliminary observations of 30 students at IKIP Mataram, found 9 students experienced mild stress, 15 students experienced moderate stress and 6 students experienced severe stress. So that research is conducted to determine the factors that influence the level of stress of students in completing the thesis. This research is a case study research with techniques and instruments of data collection using questionnaires. The sample used by 100 students was determined using purposive sampling and the analytical method used was ordinal logistic regression analysis. The results showed that the factors that influence the stress level of students in completing the thesis are confusing factors developing the theory and difficult to find literature. The ordinal logistic regression model obtained is logit (Y≤1│X) = 0.886 + 1,233X_2 + 1,865X_3 and logit (Y≤2│X) = 3,917 + 1,233X_2 + 1,865X_3. The value of e ^ (parameter X_2) = 3.4 which means that if students experience confusion in developing theories, they tend to increase stress levels by 3.4 times compared to students who do not experience confusion in developing theories